Dynamic functional connections in leukoaraiosis patients without cognitive impairment: A pilot study - Xu, Xingru; Chen, Yu-Chen; Yin, Xindao; Zuo, Taosheng; Feng, Guangkui; Xu, Kaixi (Frontiers in Aging Neuroscience, 2022)
Purpose: Leukoaraiosis is a major public issue that affects elderly adults. However, the underlying neuropathological mechanism of leukoaraiosis without cognitive impairment requires examination. The present study aimed to explore the dynamic functional network connectivity in LA patients without cognitive impairment. Methods: Twenty-three patients with leukoaraiosis and 20 well-matched healthy controls were recruited for the present study. Each subject underwent MRI scanning and cognition evaluations. Spatial independent component analysis was conducted to evaluate dynamic functional connectivity. The differences in dynamic functional network connectivity (dFNC) were determined and correlated with cognitive performance. Results: Compared with controls, leukoaraiosis without cognitive impairment showed aberrant dFNC in State 1, involving increased connectivity in the default mode network (DMN) with the executive control network (ECN). In addition, decreased connectivity in the DMN with the salience network (SN) was found in State 3. Furthermore, the decreased number of transitions between states was positively associated with the visuospatial/executive score (Spearman’s rho = 0.452, p=0.031), and the longer mean dwell time in State 1 was negatively associated with the MoCA score (Spearman’s rho = -0.420, p=0.046). Conclusion: These findings enrich our understanding of the neural mechanisms underlying leukoaraiosis and may serve as a potential imaging biomarker for investigating and recognizing the LA at early stage.